Photonic Nanojet Generation Using Integrated Silicon Photonic Chip with Hemispherical Structures - Aneesh Vincent Veluthandath; Ganapathy Senthil Murugan (Photonics, 2021)
Photonic nanojet (PNJ) is a tightly focused diffractionless travelling beam generated by dielectric microparticles. The location of the PNJ depends on the refractive index of the material and it usually recedes to the interior of the microparticle when the refractive index is higher than 2, making high index materials unsuitable to produce useful PNJs while high index favours narrower PNJs. Here we demonstrate a design of CMOS compatible high index on-chip photonic nanojet based on silicon. The proposed design consists of a silicon hemisphere on a silicon substrate. The PNJs generated can be tuned by changing the radius and sphericity of the hemisphere. Oblate spheroids generate PNJs further away from the refracting surface and the PNJ length exceeds <semantics>17λ</semantics> when the sphericity of the spheroid is 2.25 The proposed device can have potential applications in focal plane arrays, enhanced Raman spectroscopy, and optofluidic chips.